Association between negative psychology and sleep quality in dialysis patients during the COVID‐19 pandemic - Liuyan Huang; Fan Zhang; Rong Zhu; Liya Wang; Yue Zhang; Huachun Zhang; Yifei Zhong (Wiley, 2023)
Abstract Aims and Objectives The aim of this study was to assess the sleep quality in dialysis patients during the COVID‐19 epidemic and explore the association between negative psychology (including depression, anxiety, and stress) and sleep quality in this population. Design A cross‐sectional study including three centres. Methods (Patients or Public Contribution) This cross‐sectional study included 378 dialysis patients from April to May 2022 in three dialysis centres in Shanghai. Methods. Depression, anxiety, stress, and sleep quality were measured by the Hospital Anxiety and Depression Scale (HADS), Perceived Stress Scale‐14 (PSS‐14), and Pittsburgh sleep quality index (PSQI), respectively. With a threshold of 5 to classify participants into good and poor sleep quality, with HADS/PSS‐14 scores as independent variables (per standard deviation (SD) increment), respectively and binary Logistic regression model was constructed to explore the association between the three negative psychological aspects of depression, anxiety, and stress and sleep quality. Results The median PSQI score was 11.0 (mean ± SD: 11.8 ± 4.8). Among them, poor sleep quality (i.e., PSQI >5) was reported by 90.2% of participants. After adjusting for sociodemographic and disease‐related information, HADS‐depression was associated with a significant 49% (odds ratio (OR): 1.49; 95% CI 1.02-2.18) increase in the risk of poor sleep quality for each additional SD (2.4). Correspondingly, for each SD (7.1) increase in PSS‐14, the risk of poor sleep quality was significantly increased by 95% (OR: 1.95; 95% CI 1.35-2.82). Conclusion During the COVID‐19 pandemic, there was a significant negative association between negative psychology, such as depression and stress, and sleep quality in dialysis patients, and this relationship was independent of the dialysis modality. Relevance to Clinical Practice In the context of the rampant COVID‐19, the vast majority of dialysis‐dependent chronic kidney disease presents with severe sleep quality problems, and negative psychology is a potential influencing factor.